Dataset on the patterns of livelihood diversification in farming systems of the Eastern Gangetic Plains of South AsiaDataverse - Tamara M. Jackson; Ravi Nandi; Arifa Jannat; Arunava Ghosh; Dilip Kumar Hajra; Biplab Mitra; Md Mamunur Rashid; Sagar Bista; Anjana Chaudhary; Pragya Timsina; Emma Karki; Kali Ratan Chakma; et al. (Data in Brief)
The Eastern Gangetic Plains (EGP) region, characterized by smallholder-dominated farming, is experiencing rapid socio-economic and environmental changes. To enhance resilience, income stability, and food security, smallholders are increasingly diversifying their livelihoods away from traditional agriculture. However, the patterns and drivers of this diversification remain poorly understood. This study, utilizing data from the Rupantar project, aims to elucidate these patterns, identify key drivers, and assess the impacts on productivity, profitability, nutrition, and inclusion. A mixed-methods approach was employed, including a baseline survey of 1400 households across India, Nepal, and Bangladesh and analysis using the Simpson's Index of Diversity (SID). Fractional regression models revealed moderate diversification levels across the EGP with significant geographical and contextual variability. Key drivers included access to resources, gender, education, market access, and institutional support, with differences observed across countries and diversification types. Factors such as non-ownership of irrigation pumps, female household headship, and engagement in off-farm activities were significant predictors of higher diversification. The study found that diversification can enhance income security, nutritional outcomes, and environmental sustainability, although impacts vary by diversification type.